Inhibition of lymphangiogenesis impairs antitumour effects of photodynamic therapy and checkpoint inhibitors in mice. (September 2017) - Muchowicz, Angelika; Wachowska, Malgorzata; Stachura, Joanna; Tonecka, Katarzyna; Gabrysiak, Magdalena; Wołosz, Dominika; Pilch, Zofia; Kilarski, Witold W.; Boon, Louis; Klaus, Tomasz J.; Golab, Jakub
Abstract: Photodynamic therapy (PDT) has been shown to destroy tumour-associated lymphatic vessels. Therefore, we sought to investigate the functional outcomes of PDT-mediated damage to the lymphatic vessels. We observed that PDT with verteporfin, completely but transiently, blocks the functional lymphatic drainage in the orthotopic mammary tumour models. Sustained inhibition of lymphatic vessels regeneration induced by lenalidomide or the soluble form of vascular endothelial growth factor receptor 3 (sVEGFR3) that neutralises lymphangiogenic vascular endothelial growth factor C (VEGF-C), significantly impaired antitumour efficacy of PDT. Antilymphangiogenic compounds also significantly inhibited the ability of intratumourally inoculated dendritic cells (DCs) to translocate to local lymph nodes and diminished the number of tumour-infiltrating interferon-γ-secreting or tumour antigen-specific CD8 + T cells. Lenalidomide also abrogated antitumour effects of the combination immunotherapy with PDT and anti-programmed death-ligand 1 (PD-L1) antibodies. Altogether, these findings indicate that PDT-mediated damage to the lymphatic vessels negatively affects development of antitumour immunity, and that drugs that impair lymphatic vessel regeneration might not be suitable for the use in combination with PDT. Highlights: Lenalidomide diminishes antitumour efficacy of PDT, impairs recovery of tumour lymphatic vessels damaged by PDT and decreases PDT-induced antitumour immune response. Anti-PD-L1 antibodies significantly potentiate antitumour effects of verteporfin-PDT and lenalidomide almost completely abrogates the antitumour efficacy of the combination. PDT efficacy is completely abrogated by the soluble vascular endothelial growth factor receptor 3.